Study of smoke movement characteristics in tunnel fires in high‐altitude areas - Yan, Guanfeng; Wang, Mingnian; Yu, Li; Tian, Yuan; Guo, Xiaohan (Fire and materials, 2020)
Summary Understanding smoke temperature distributions and transport characteristics is of great importance to control and exhaust thermal‐driven smoke. However, previous studies have focused on this problem in plain areas, whereas ambient pressure decreases as elevation increases. This study investigates the influence of ambient pressure on the hot gas temperature distribution and movement characteristics in a tunnel fire. A series of numerical simulations are carried out in a vehicle tunnel with various heat release rates (HRRs) and ambient pressures. The results show that the maximum temperature and longitudinal temperature distribution under the tunnel ceiling increase with decreasing ambient pressure due to less heat loss caused by lower air density. In addition, the vertical temperatures of the smoke are slightly higher under lower ambient pressure, and this phenomenon makes the smoke spread slightly faster while the smoke layer thickness remains nearly the same under different ambient pressures. The results can provide a reference for tunnel lining design and ventilation arrangements in high‐altitude areas.